1999
DOI: 10.1099/00207713-49-2-367
|View full text |Cite
|
Sign up to set email alerts
|

Marinobacter aquaeolei sp. nov., a halophilic bacterium isolated from a Vietnamese oil-producing well

Abstract: Several strains of moderately halophilic and mesophil ic bacteria were isolated a t the head of an oil-producing well on an offshore platform in southern Vietnam. Cells were Gram-negative, non-spore-forming, rod-shaped and motile by means of a polar f lagellum. Growth occurred a t NaCl concentrations between 0 and 20%; the optimum was 5% NaCl. One strain, which was designated VT8l, could degrade n-hexadecane, pristane and some crude oil components. It grew anaerobically in the presence of nitrate on succinate,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
119
1
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 203 publications
(128 citation statements)
references
References 44 publications
5
119
1
2
Order By: Relevance
“…Marinobacter species are Gram-negative, halophilic bacteria able to grow heterotrophically on a wide range of substrates with oxygen or nitrate as a terminal electron acceptor (Gauthier et al, 1992;Huu et al, 1999). Although it has previously been demonstrated that Marinobacter species are phylotypes from the n-hexane and toluene enrichment cultures performed with TB, ML and LD sediments, and of the toluenedegrading denitrifiers isolated from NS and BS sediments, with selected reference sequences of the proteobacteria.…”
Section: Enrichment Culturementioning
confidence: 99%
“…Marinobacter species are Gram-negative, halophilic bacteria able to grow heterotrophically on a wide range of substrates with oxygen or nitrate as a terminal electron acceptor (Gauthier et al, 1992;Huu et al, 1999). Although it has previously been demonstrated that Marinobacter species are phylotypes from the n-hexane and toluene enrichment cultures performed with TB, ML and LD sediments, and of the toluenedegrading denitrifiers isolated from NS and BS sediments, with selected reference sequences of the proteobacteria.…”
Section: Enrichment Culturementioning
confidence: 99%
“…Several species of the genus Marinobacter (i.e. Marinobacter aquaeolei, Marinobacter maritimus and Marinobacter algicola) have been associated with aromatic and aliphatic hydrocarbon degradation [1,2,[9][10][11]. This may indicate a functional role in the organic carbon cycle, as they constitute one of the dominant bacterial community groups in contaminated environments [12].…”
mentioning
confidence: 99%
“…A further 19 species with validly published names have subsequently been included within the genus (Antunes et al, 2007; Gorshkova et al, 2003;Green et al, 2006;Gu et al, 2007;Guo et al, 2007; Kim et al, 2006;Liebgott et al, 2006;Martin et al, 2003; Romanenko et al, 2005;Shieh et al, 2003;Shivaji et al, 2005;Xu et al, 2008;Yoon et al, 2003Yoon et al, , 2004Yoon et al, , 2007; Marinobacter aquaeolei (Huu et al, 1999) has been proposed to be a synonym of Marinobacter hydrocarbonoclasticus (Marquez & Ventosa, 2005). These species are motile, halophilic, Gram-negative gammaproteobacteria isolated from saline terrestrial or, more typically, marine environments.…”
mentioning
confidence: 99%